Metamorfose Nisan Aceh, Dari Masa Ke Masa - Repelita Wahyu Oetomo (Balai Arkeologi Sumatera Utara, 2016)
AbstractTombstones in Aceh have gone through changes of shapes (metamorphosis) from simple shapes to the shapes like we know today. The metamorphosis began with some simple tombstones like the ones at Samudera Pasai, the starting point of Islam dispersal in the archipelago. Until now Samudera Pasai is believed to be the first Islamic kingdom in the archipelago, which made it a place to adopt the shapes of tombstones from the earlier period, which is the Hindu-Buddhist period. Other places that are thought to be the earliest Islam areas in the archipelago include among others Lamreh/Lamuri in Aceh Besar and Peureulak,but the types of tombstones being adopted are not as many as at Samudera Pasai. The changes that occur are the addition of several parts gradually until like present form. Some types of tombstones developed ranging from decorative patterns up to size progress. But, some types of tombstones in recent times never appeared again. Tombstones, which called the